Lorentzian quantum gravity and the graviton spectral function - Fehre, Jannik; Litim, Daniel F.; Pawlowski, Jan M.; Reichert, Manuel (Physical review letters, 2023)
We present the first direct and nonperturbative computation of the graviton spectral function in quantum gravity. This is achieved with the help of a novel Lorentzian renormalization group approach, combined with a spectral representation of correlation functions. We find a positive graviton spectral function, showing a massless one-graviton peak and a multigraviton continuum with an asymptotically safe scaling for large spectral values. We also study the impact of a cosmological constant. Further steps to investigate scattering processes and unitarity in asymptotically safe quantum gravity are indicated.
Veröffentlicht: 24. Februar 2023
Gesehen am 24.07.2023